2016
DOI: 10.3389/fmicb.2016.01785
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Cyanide in the Rhizosphere: Not Suppressing Plant Pathogens, but Rather Regulating Availability of Phosphate

Abstract: Plant growth promoting rhizobacteria produce chemical compounds with different benefits for the plant. Among them, HCN is recognized as a biocontrol agent, based on its ascribed toxicity against plant pathogens. Based on several past studies questioning the validity of this hypothesis, we have re-addressed the issue by designing a new set of in vitro experiments, to test if HCN-producing rhizobacteria could inhibit the growth of phytopathogens. The level of HCN produced by the rhizobacteria in vitro does not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(126 citation statements)
references
References 60 publications
4
122
0
Order By: Relevance
“…In a recent study by Rijavec and Lapanje (2016) have shown that there is no correlation between the amount of HCN produced by a particular strain and its ability to inhibit the growth of phytopathogenic bacteria or fungi. These workers proposed a new role for HCN production by rhizospheric bacteria.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
“…In a recent study by Rijavec and Lapanje (2016) have shown that there is no correlation between the amount of HCN produced by a particular strain and its ability to inhibit the growth of phytopathogenic bacteria or fungi. These workers proposed a new role for HCN production by rhizospheric bacteria.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
“…The inhibition of phytopathogenic fungi was correlated with plant growth promotions, and subsequently, HCN producer strains seemed to be very attractive biocontrol agents (Voisard et al ). A very recent study, however, showed in vitro that rhizobacterial HCN did not correlate with the biocontrol effect but instead acted via sequestration of metal ions and indirectly caused an increase of phosphate availability (Rijavec and Lapanje ).…”
Section: Biological Effects Of Microbial Inorganic Volatile Compoundsmentioning
confidence: 99%
“…The cyanide ion is a potent inhibitor of many metalloenzymes, especially copper-containing cytochrome c oxidases 85 . In addition to a role in the control of plant diseases 6 , cyanide may play a role in increasing the availability of nutrients for plants through its ability to sequestrate metal ions 86 . Dimethyl sulfide, produced by the rhizospheric bacteria P. fluorescens and S. plymuthica , has bacteriostatic effects on the plant pathogens Agrobacterium tumefaciens and Agrobacterium vitis 87 .…”
Section: War In the Rhizospherementioning
confidence: 99%